Anti- and Protumorigenic Effects of PPARγ in Lung Cancer Progression: A Double-Edged Sword - Howard Li; Mary C. M. Weiser-Evans; Raphael Nemenoff (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPARγ) is a member of the nuclear receptor superfamily of ligand-activated transcription factors that plays an important role in the control of gene expression linked to a variety of physiological processes, including cancer. Ligands for PPARγ include naturally occurring fatty acids and the thiazolidinedione class of antidiabetic drugs. Activation of PPARγ in a variety of cancer cells leads to inhibition of growth, decreased invasiveness, reduced production of proinflammatory cytokines, and promotion of a more differentiated phenotype. However, systemic activation of PPARγ has been reported to be protumorigenic in some in vitro systems and in vivo models. Here, we review the available data that implicate PPARγ in lung carcinogenesis and highlight the challenges of targeting PPARγ in lung cancer treatments.